INOVASI PELAYANAN PUBLIK “MENCARI KEKASIHKU” DI DISPENDUKCAPIL KABUPATEN GROBOGAN - Safitri, Aprilia Dewi; ., Maesaroh; Widowati, Nina (Journal of Public Policy and Management Review, 2024)
Innovation of “Mencari Kekasihku” is an innovation at the Population and Civil Registration Office of Grobogan Regency aimed at improving the validity of population data on changes in marital status among muslim residents in Grobogan Regency. This study aims to identify and analyze the characteristics of the public service innovation “Mencari Kekasihku” at the Population and Civil Registration Office of Grobogan Regency, as well as identify the supporting and inhibiting factors of the public service innovation “Mencari Kekasihku" at the Population and Civil Registration Office of Grobogan Regency. This research uses a qualitative descriptive method with data collection techniques including interviews, observations, and documentation. The results show that the public service innovation “Mencari Kekasihku" at the Population and Civil Registration Office of Grobogan Regency has been running well in terms of relative advantage, compatibility, and observability, although there are still obstacles in its implementation in terms of complexity and trialability. Supporting factors for the innovation “Mencari Kekasihku" include the desire for self-improvement, freedom of expression, and infrastructure. Meanwhile, inhibiting factors for the innovation “Mencari Kekasihku" include the lack of recognition or incentives, as well as administrative pressures and barriers.